Evaluation of activities and instrumental activities of daily living and correlated factors of traumatic brain injury patients in Vietnam - Anh Thuy Hoang; Tung Hoang Tran; Hai Minh Vu; Hoa Thi Do; Thuc Minh Thi Vu; Linh Gia Vu; Cuong Tat Nguyen; Huyen Phuc Do; Carl A. Latkin; Roger C. M. Ho; Cyrus S. H. Ho (Scientific Reports, 2024)
Abstract Traumatic brain injury (TBI) is among the leading causes of death in Vietnam. Survivors of TBI suffer from functional and cognitive deficits. Understanding that Activities of Daily Living (ADLs) and Instrumental Activities of Daily Living (IADLs) are crucial in measuring the treatment and health-related quality of life among patients with TBI. This study aims to evaluate ADLs and IADLs among the TBI population in Vietnam and determine the correlated factors to these two indices. A cross-sectional study was conducted on 212 patients with TBI in Vietnam from February to September 2020. ADLs and IADLs scales were applied. Depression, quality of sleep, and social support scales were used. Multivariate Tobit regression was adopted to identify factors associated with ADLs and IADLs. Patients who received first aid had higher ADLs scores than those who had not, by a statistical difference with a p value = 0.04. The mean ADLs score was 5.4 (SD = 1.4). The mean score of IADLs was 7.3 (SD = 1.7). Female patients (Mean = 7.6, SD = 1.1) performed better in IADLs than male patients (Mean = 7.1, SD = 1.9). Both ADLs and IADLs were affected strongly by depression and Injury Severity scores (p < 0.01), whereas IADLs were significantly correlated to caregiver types and quality of sleep (p < 0.01). Family support was observed as a negatively correlated factor to IADLs. Findings from the study provided evidence for authorities to adjust the health strategies among patients with TBI. Proper prehospital care, a basic low-cost hospital care model, and mental health counseling services should be considered when developing health interventions in Vietnam.